Monetary union in West Africa (ECOWAS) : is it desirable and how could it be achieved? - Masson, Paul R.; Pattillo, Catherine A.; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
In April 2000 six West African countries declared their intention to proceed to monetary union among the non-CFA franc countries of the region by January 2003, as a first step toward a wider monetary union including all the ECOWAS countries in 2004. The purpose of this paper is to evaluate whether a monetary union makes economic sense, to discuss the institutional requirements for successful monetary union and to consider how best the political momentum for a union can be channeled toward a fundamental improvement in underlying policies.
lje 21/07/2016
Loans
Keywords: Monetary unions; Africa, West